IMPLEMENTASI PENDIDIKAN INKLUSI BERBASIS PENGEMBANGAN DIRI KELAS 2 DI SD DWIJENDRA MATARAM - Nurhidayah; Istiningsih, Siti; Novitasari, Setiani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The purpose of this study was to determine to describe the preparation of teachers in implementing self-development-based Inclusive Education at SD Dwijendra Mataram. The type of research used is qualitative research, with descriptive methods. The research population was 1 principal, 1 special supervisor teacher, and 1 class teacher. Data collection uses interview sheets, observation sheets and documentation sheets. The results of data analysis Planning carried out at SD Dwijendra Mataram is that there is no special work program for special assistance teachers, there is only coaching, which is carried out 2 times a week, after school